Strengthening the Somaliland health system by integrating public and private sector family medicine - Muna M. Mahfud; Fathia M. Nour; Hodan J. Abdi; Sabah M. Muse; Tim Fader (AOSIS, 2021)
Four family physicians, who received their specialty training at Amoud University in Somaliland, organised a practice together that uses informal public-private partnerships to optimise their clinical care and teaching. Their experience offers insights into public-private partnerships that could strengthen the country's healthcare system.